The Effect of Investor Sentiment toward an Exchange Merger on Liquidity - Hisada, Takanori (International Journal of Economics and Financial Issues, 2018)
This study investigates the relationships among an exchange merger, investor sentiment, and liquidity by analyzing data from the 2013 merger of the Tokyo Stock Exchange and Osaka Securities Exchange. In contrast to prior studies, this study considers the investor sentiment eï¬€ect of the merger. Synergy and the investor sentiment eï¬€ect occur in the short run with liquidity increases. The investor sentiment eï¬€ect occurs more strongly in small stocks. Keywords: Investor sentiment, Exchange merger, Liquidity JEL Classifications: G40, G10, G19